Hercules furens - Seneca, Lucius Annaeus, approximately 4 B.C.-65 A.D. (Mnemosyne, Supplements, 1999)
This is most comprehensive study of Seneca's Hercules Furens to date and indeed of any Roman tragedy. Apart from illustrating the poetic language, the literary conventions and the dramatic technique of the play, the book highlights the figure of the Roman Hercules in relation to its Greek model, the Euripidean Herakles. The comprehensive introduction on myth, modern interpretations and textual transmission of the play is followed by a discussion of the newly discovered collation of the codex Etruscus by J.F. Gronovius. The detailed commentary is provided with a new critical edition and a new German translation. The work includes a full bibliography, an analytical index and a complete index of passages cited. Special attention is given to literary motifs and topoi as well as to Seneca's poetic language in its pivotal position between the Augustan poets and Neronian-Flavian epic.